General and oral characteristics of Rett syndrome: case report - Pereira, Karina Gesuele; Alves, Gisele Rafael; Jóias, Renato Morales; Josgrilberg, Erika Botelho; Jóias, Renata Pilli (Brazilian Dental Science, 2017)
Introduction: Rett syndrome is a neurodegenerative disease that affects females of all races worldwide. It is the second most frequent cause of mental disability in girls. Objective: To describe the general and oral characteristics at stage three. Case report: A girl aged seven years and seven months, leukoderma, coming from Vallo della Lucania, Salerno, Italy was at the stage three of Rett syndrome. At the first stage, from six to eighteen months of life, the girl ate by herself, but she did not walk. At the second stage, from eighteen months of life, she started the ataxic gait and stopped talking. At the third stage, she had the reduction of the autist behavior, improved the eye contact, smile and communicative abilities. The genetic examination revealed de novo mutation, that is, without inheritance. Conclusion: Rett syndrome lacks specific treatment. Adjuvant therapies include physiotherapy, hydrotherapy, occupational therapy, music therapy, equine therapy, as well as therapies to treat some symptoms. A multidisciplinary treatment is required. The prognosis consists of following-up the individual throughout life, treating the symptoms. Keywords: Autistic Disorder, Chronic disease, Epilepsy, Intellectual Disability, Rett Syndrome.